Prolonged Honeymoon Phase in Adult-Onset Type 1 Diabetes Mellitus: A Case Study - Pranjali Shah (Journal of Diabetology)
Abstract Type 1 diabetes mellitus (T1DM) exhibits heterogeneity in presentation, and the “honeymoon” period, characterized by temporary beta-cell function restoration, is a significant aspect influencing disease progression. Adult-onset T1DM differs from pediatric cases, with complete insulin withdrawal being rare. This study investigates a 23-year-old female positive for glutamic acid decarboxylase (GAD) antibodies to assess the potential for an extended honeymoon phase. The patient, without significant medical history, presented with recurrent boils, notable weight loss, and had a family history of diabetes (maternal grandmother). Laboratory results showed uncontrolled hyperglycemia, absence of C-peptide, and positive for anti-GAD. Treatment involved CGMS fixation and insulin degludec/aspart, leading to excellent sugar control. Notably, insulin dosage reduction and improved C-peptide levels occurred over two years. This case highlights the complexity of T1DM presentations, the potential for extended honeymoon phases, and emphasizes the need for personalized management. Ongoing research into honeymoon phase determinants and genetic aspects will refine the understanding and optimize care for autoimmune diabetes.